On Fuzzy Subhypernear-Ring - AbouElwan, Yasser; Sanaa Qadous; Samah Qadous (AlQalam Journal of Medical and Applied Sciences, 2024)
In this study, two main goals were achieved. In near-ring N, we have proven that, the level set is a subnear-ring of N if and only if the fuzzy set is the fuzzy subnear-ring of N. Similarly, in hyper near-ring R, it has been proven that, a fuzzy set is a fuzzy hypernear-ring if and only if level set is a sub-hypernear-ring of R. A direct proof method was used to reach these results, which will contribute to expanding the field of study on fuzzy near-ring and fuzzy hyper near-rings. في هذه الدراسة، تم تحقيق هدفين، في قريب الحلقة، تم أثبات أن، المجموعة المنسوبية تكون قريب الحلقة الجزئية لقريب الحلقة اذاواذا فقط كانت المجموعة الضبابية هي قريب الحلقة الضبابية. بالمثل في قريب الحلقة الضبابية تم أثبات أن، المجموعة الضبابية تكون قريب الحلقة الضبابية اذا واذا فقط كانت المجموعة المنسوبية هي قريب الحلقة الفوقية الجزئية لقريب الحلقة الفوقية. تم استخدام أسلوب البرهان المباشر للوصول لهذه النتائج، التي ستسهم في توسيع مجال الدراسة حول قريب الحلقات الضبابية والفوقية الضبابية